CDKL5 deficiency disorder in males: Five new variants and review of the literature. (July 2021) - Siri, Barbara; Varesio, Costanza; Freri, Elena; Darra, Francesca; Gana, Simone; Mei, Davide; Porta, Francesco; Fontana, Elena; Galati, Giulia; Solazzi, Roberta; Niceta, Marcello; Veggiotti, Pierangelo; et al.
Abstract: The X-linked Cyclin-Dependent Kinase-Like 5 ( CDKL5 ) gene encodes a serine-threonine kinase highly expressed in the developing brain. Loss of function of CDKL5 is pointed out to underlie the CDKL5 Deficiency Disorder (CDD), an X-linked dominant disease characterized by early-onset epileptic encephalopathy and developmental delay, usually affecting females more than males. To the best to our knowledge, only 45 males with CDD have been reported so far. Type and position of CDKL5 variants with different impact on the protein are reported to influence the clinical presentation. X-chromosome inactivation occurring in females and post-zygotic mosaicism in males are also believed to contribute to this variability. Based on these issues, genotype-phenotype correlations are still challenging. Here, we describe clinical features of five additional affected males with unreported CDKL5 variants, expanding the molecular spectrum of the disorder. We also reviewed the clinical profile of the previously reported 45 males with molecularly confirmed CDD. Severe developmental delay, cortical visual impairment, and early-onset refractory epilepsy characterize the CDD picture in males. By assessing the molecular spectrum, we confirm that germ-line truncating CDKL5 variants, equally distributed across the coding sequence, are the most recurrent mutations in CDD, and cause the worsen phenotype. While recurrence and relevance of missense substitutions within C-terminal remain still debated, disease-causing missense changes affecting the N-terminal catalytic domain correlate to a severe clinical phenotype. Finally, our data provide evidence that post-zygotic CDKL5 mosaicism may result in milder phenotypes and, at least in a subset of subjects, in variable response to antiepileptic treatments.